Radiation therapy and chemotherapy of mediastinal tumors: Round table abstract - Sica, Miguel Angel (Cirugía del Uruguay, 1974)
In most of the sick you see in the clinic with mediastinal tumors, of agree, with our experience. radiotherapy It is the treatment of choice.